Vistunarmat aldraðra í Reykjavík 1992 - Gróa Björk Jóhannesdóttir; Pálmi V. Jónsson (Læknafélag Íslands, Læknafélag Reykjavíkur, 2009)
Neðst á síðunni er hægt að nálgast greinina í heild sinni með því að smella á hlekkinn View/Open No-one can be admitted to a nursing home in Iceland without a prior assessment of need, that is standardized in content and method. In 1992 there were 546 individuals in Reykjavik assessed in a need for nursing home placement, 304 (55.7%) in an unskilled (UNH) and 242 (44.3%) in a skilled nursing home (SNH). The mean age was 81.6 (±0.4) and 81.8 (± 0.5) years, respectively, with the same female: male ratio of 2:1. On January 1st 1993, 19.4 per 1000 inhabitants in Reykjavik 65 years of age or older were waiting for admission to an UNH, where¬as 14.1 per 1000 waited for a SNH admission. Those who were waiting for an UNH had mostly social difficulties along with affective symtoms, but those who were waiting for a SNH, had in addition to social difficulties, impaired physical and mental capacity with greater functional deficits. The PNHA was simplified with each of the twelve variables divided into a lower and higher level of difficulty. A logistic regressions analysis found seven independent variables predicting SNH placement: physical health, use of medications, dementia, mobility, abil¬ity to eat, ability to dress and groom, control of urine and stools. Of those assessed in a need for SNH 78.5% had dementia of some degree. Physical function and mobility appear to be relatively preserved until late in the dementia. These analyses confirm the validity of a PNHA, which is based on disabilities in four domains: social, physical, mental and functional health. Nú má enginn vistast til langdvalar á öldrunarstofnun nema að undangengnu faglegu mati á þörf. Greinin lýsir gögnum vistunarmatsins í Reykjavik árið 1992, en þá voru 546 einstaklingar metnir í þörf fyrir vistun, 304 (55,7%) í þjónustuhúsnæði og 242 (44,3%) í hjúkrunarrými. Meðalaldur metinna var 81,6 ár (±0,4) í þjónustuhópi og 81,8 ár (±0,5) í hjúkrunarhópi, en kynhlutfall var tvær konur á móti einum karli í báðum hópum. Um áramótin 1992-1993 biðu 19,4 af hverjum ...